Sampling of micro and nano particles from aerosols generated during dental interventions - Kuzmanović, Miloš; Puškar, Tatjana; Djurovic Koprivica, Daniela; Ilić Micunović, Milana; Budak, Igor; Vukelić, Djordje (Journal of Production Engineering, 2022)
Dentists and dental team members are exposed to an increased risk of large amounts of aerosols in the working atmosphere during clinical dental procedures. The analysis of the part of the aerosol that includes the finest particles of micro and nano dimensions is a starting point for understanding the relationship between exposure to aerosols and negative effects on the health of dentists. The paper presents the methodology and experimental realization of clinical sampling of micro and nano particles, from the aerosol generated during dental interventions, using a personal sampler.